Pasang Surut Komisi Yudisial: Kreasi, resistensi dan restorasi - Umi Illiyina (Jurnal Konstitusi, 2011)
In The Federalist Papers (1787), James Madison said: “If the angels to govern men, then the internal and external monitoring is not necessary”. In other words, the control is absolute. Supervisory authority weaknesses of the institution in vast expanses of the judiciary, as well as pave the way for the “dictatorship of the courts”. The Judicial Commission is present    to prevent the dictatorship of the Court. With all the hope and resistance  to the Judicial Commission, it remains a small candle in the corner of a coveted judicial building clean, independent and   authoritative.